The hammered dulcimer: poems - Williams, Lisa, author; Utah State University Press, publisher (Colorado State University. Libraries, 1998)
Lisa William's poems are infused with what John Hollander calls a guarded wonder." A poet of unique vision, she seems always to be "looking at," with special attention to the experience of the senses. Moreover, Williams is equally concerned with epistemology--the how of seeing. And it is perhaps this quality of attention that informs her interest in the formulations of poetry itself, in its constructed dimension. Her control of the line, of rhythmic possibilities, of structures both formal and free, is evident in every poem. Together, William's original voice and her poetic finesse allow her to create those harmonies of wonder evoked by the very instrument, the hammered dulcimer, that gives her collection its name. Judge for the 1998 May Swenson Poetry Award was John Hollander, poet, critic, professor. Long a major figure in American letters, Hollander was a personal friend to May Swenson, and has influenced the work of many of our best emerging poetic voices.--Provided by publisher.
The direction of shadow -- Sunday morning -- Interruption of flight -- Yellow bird -- What the wind said to the girl who was afraid -- The fall -- The tenderness -- The hammered dulcimer -- Complaint -- Eve, after eating -- Man walking -- Black horses -- The growth -- Manners, 1977 -- A spider -- The man by the river -- Banquet -- To night -- On the nature of beauty -- Romantic relief -- Negation -- Landscape -- A wind in place -- Crater -- On a worm descending a thread -- A story of swans -- God put the noose around my neck -- The grasshopper -- The end of spring -- In the abstract -- Ambivalence -- The chant -- A forward spring -- Rattlesnake -- In the valley -- After a line of Plato.
Keywords: American literature